Critical-Biographic Essay Genre - Akhmedova Shoira Nematovna (Genius Journals, 2021)
The historical-biographical method is the leading direction of literary criticism, and it withdraw the task of the criticism to cover the life and work of the writer perfectly in harmony with his time and environment. In the history of world literary criticism this method has been widely developed since the beginning of the 19th century. It is known that such historical and biographical scientists as St. Byev, A. Veselovsky, A. Morua, M. Bakhtin, M. Khrapchenko, L. Timofeev, V. Shklovsky, I. Andronnikov have accumulated rich scientific and creative experience. If we look at the history of Uzbek literary criticism, which has a rich heritage, there is clear evidence that his experiences in this series appeared much earlier - in the XV century and even earlier. In the historical-biographical method, the scale of the attitude to the creative way of life plays an important role. In any case, this scale is very narrow - if the biographical evidence is applied to certain analytical elements; in which the scale is somewhat broad, but the system of biographical evidence is preferred, and in the other, the scale is broad, the biographical evidence is analyzed in harmony with the creative personality and the environment and time. It uses both memories and adventures, as well as reflections on the reason and history of the work, as well as an analysis of individual works. According to these characteristics, critical works in this direction are manifested in four forms: 1. Literary-critical portrait - article. 2. Literary portrait. 3. Critical - biographical essay. 4. Essays. It should be noted that all four views are based on a scientific-historicalbiographical approach. This is their common denominator. The nature of the historical-biographical direction requires the consistency of evidence and scientific conclusions about the scientific-biography of the writer in literary-critical works, as well as the improvement of the evolutionary process. Discussion of the ability to effectively use the experience of theoretical thinking of the world and Russian, fraternal peoples in scientific and biographical works of the historical-biographical method plays an important role in determining the place of this direction in the history of Uzbek literary criticism. In the article, we discuss one of the genres in this direction is critical - biographical essay, its peculiarities, nature and development.
Keywords: Literary criticism; historical-biographical method; biographical evidence; critical-biographical essay